2016
DOI: 10.1016/j.cptl.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

School engagement and burnout in a sample of Brazilian students

Abstract: Objective: Some studies have suggested that school engagement can be an ally in the prevention of psychosocial and occupational risks, to which students are exposed daily. The aim of this study is to estimate the impact of emotional, behavioral, and cognitive engagement on burnout syndrome among pharmacy undergraduate students. Methods: A total of 363 students enrolled in the pharmacy undergraduate program in the College of Pharmaceutical Sciences at Sao Paulo State University's Araraquara Campus (UNESP) parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
8
1
1
Order By: Relevance
“…In another study examining the effect of university students' school engagement on exhaustion, Arlinkasari, Akmal, and Rauf (2017) reported that school engagement associated a moderately significant relationship with burnout and school engagement revealed 40% of the burnout variance. Unlike the findings of this research, Zucoloto, de Oliveira, Maroco, and Campos (2016) found that there was a moderate and negative relationship between university students' levels of behavioural and affective engagement and their burnout. These two subscales of engagement explains 81% of the variance in burnout and the cognitive engagement dimension has no significant effect on burnout.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study examining the effect of university students' school engagement on exhaustion, Arlinkasari, Akmal, and Rauf (2017) reported that school engagement associated a moderately significant relationship with burnout and school engagement revealed 40% of the burnout variance. Unlike the findings of this research, Zucoloto, de Oliveira, Maroco, and Campos (2016) found that there was a moderate and negative relationship between university students' levels of behavioural and affective engagement and their burnout. These two subscales of engagement explains 81% of the variance in burnout and the cognitive engagement dimension has no significant effect on burnout.…”
Section: Discussioncontrasting
confidence: 99%
“…Ergenlik döneminde akademik beklentilerin artması, çeşitli toplumsal rolleri öğrenme ve bu rollere uyum sağlama gibi giderek artan karmaşık durumlarla başa çıkma güçlüğü ergenin yaşantısını stres verici deneyimlere açık hale getirmektedir (Ge, Lorenz, Conger, Elder ve Simons, 1994). Ergenin aileden sonraki ilk sosyal ortamı olarak okul, bu deneyimlerin açıkça gözlenebildiği önemli bir etkileşim alanı olarak karşımıza çıkmaktadır (Salmela-Aro, Muotka, Alho, Hakkarainen ve Lonka, 2016;Salmela-Aro, Upadyaya, Hakkarainen, Lonka ve Alho, 2017;Zucoloto, de Oliveira, Maroco ve Campos, 2016).…”
Section: Introductionunclassified
“…The USEI consists of 32 items distributed in a three-factor structure covering behavioral, emotional, and cognitive engagement [ 1 ]. Behavioral engagement refers to student participation in both classroom and extracurricular activities; emotional engagement covers students’ feelings of agreement or disagreement with teachers’ instructions, and cognitive engagement refers to the commitment and vigor expended by students to understand complex concepts and put them into practice [ 1 , 5 ]. The 32-item USEI, originally proposed by Maroco et al [ 1 ], did not show a good adjustment when validated with Portuguese university students in the areas of social, biological, and exact sciences, and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors refined the instrument and obtained a reduced scale of tri-factorial structure containing 15 items. In Brazil, this instrument was validated with pharmacy-biochemistry students [ 5 ].…”
Section: Introductionmentioning
confidence: 99%